Promoting Public Health through State Cancer Control Plans: A Review of Capacity and Sustainability - Marcia G Ory; Brigid eSanner; Deborah eVollmer Dahlke; Cathy eMelvin (Frontiers Media S.A., 2015)
The Centers for Disease Prevention and Control's National Comprehensive Cancer Control Program oversees Comprehensive Cancer Control (CCC) programs designed to develop and implement CCC plans via CCC coalitions, alliances or consortia of program stakeholders. We reviewed 40 up-to-date plans for states and the District of Columbia in order to assess how capacity building and sustainability, two evidence-based practices necessary for organizational readiness, positive growth, and maintenance are addressed. We employed an electronic key word search, supplemented by full text reviews of each plan to complete a content analysis of the CCC plans. Capacity is explicitly addressed in just over half of the plans (53%), generally from a conceptual point of view, with few specifics as to how capacity will be developed or enhanced. Roles and responsibilities, timelines for action, and measurements for evaluation of capacity building are infrequently mentioned. Almost all (92%) of the 40 up-to-date plans address sustainability on at least a cursory level, through efforts aimed at funding or seeking funding, policy initiatives and/or partnership development. However, few details as to how these strategies will be implemented are found in the plans. We present the Texas plan as a case study offering detailed insight into how one plan incorporated capacity building and sustainability into its development and implementation. Training, technical assistance, templates and tools may help CCC Coalition members address capacity and sustainability in future planning efforts and assure the inclusion of capacity building and sustainability approaches in CCC plans at both the state, tribal, territorial and jurisdiction levels.